Verification of the Short-Term Impact of Imeglimin on Liver Fibrosis Markers Stratified by Liver Fibrosis Risk in Patients With Type 2 Diabetes - Tanaka, Takumi; Kitao, Takashi; Kubori, Motohiro; Komoda, Yoshio; Mori, Yukiko; Ibata, Takeshi (Curēus (Palo Alto, CA), 2025)
Objective This study aimed to evaluate the effects of imeglimin on Fibrosis-4 index (FIB-4) and aspartate aminotransferase to platelet ratio index (APRI) across three subgroups classified according to the FIB-4 classification for assessing liver fibrosis risk in patients with type 2 diabetes mellitus (T2DM). Materials and methods Eighty-three patients with T2DM were classified into three subgroups based on their FIB-4 at the initiation of imeglimin, following the FIB-4 classification: Group 1 (G1) (FIB-4 < 1.30, n = 25), Group 2 (G2) (1.30 ≤ FIB-4 < 2.67, n = 44), and Group 3 (G3) (FIB-4 ≥ 2.67, n = 14). Then we evaluated the changes (Δ) in FIB-4 and APRI three months after the initiation of imeglimin in each subgroup. Subsequently, ΔFIB-4 and ΔAPRI were compared across the three subgroups. Baseline parameters and their changes correlated with ΔFIB-4 were also analyzed. Results FIB-4 significantly decreased in G2 (p = 0.046) and G3 (p = 0.017), while APRI showed significant reductions across all three subgroups (G1: p = 0.007, G2: p < 0.001, G3: p = 0.002). ΔFIB-4 in G3 was significantly greater than that observed in G1 (p = 0.01), and ΔAPRI in G3 was significantly greater than those in G1 (p = 0.004) and G2 (p = 0.007). ΔFIB-4 was negatively correlated with baseline FIB-4 and Triglycerides (TG), and positively correlated with Δγ-glutamyl transpeptidase (γ-GTP). Conclusions The short-term effects of imeglimin on FIB-4 and APRI in patients with T2DM may be more pronounced in patients with higher baseline FIB-4 levels.